ASSESSMENT OF LENGTH-WEIGHT RELATIONSHIPS, CONDITION FACTOR, AND GROWTH PATTERNS OF Clarias gariepinus AND Oreochromis niloticus IN SABKE RESERVOIR, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2025)
Sabke Reservoir in Katsina State, Nigeria, is a crucial water body supporting agriculture, fisheries, and domestic use, but faces increasing ecological stress due to anthropogenic activities, prompting the need to assess its physicochemical status and environmental health. This study investigated the length-weight relationship (LWR), condition factor (K), and growth pattern of two economically important freshwater fish speciesClarias gariepinus and Oreochromis niloticusfrom the Sabke Reservoir, Katsina State, Nigeria, between June and November 2024. A total of 120 specimens (60 per species) were collected and analyzed to determine growth dynamics and physiological condition using standard morphometric methods. Results revealed negative allometric growth in both species, with b-values less than 3 across sexes and combined groups. In C. gariepinus, females exhibited a higher b-value (2.18) and condition factor (1.27) than males (b = 1.54; K = 1.15), suggesting better health and consistent growth in females. Similarly, O. niloticus demonstrated higher b-values and strong length-weight correlations (r 0.740.75), with condition factor values exceeding 3.1 for both sexes, indicating excellent physiological status and adaptation to the reservoir environment. Comparatively, O. niloticus showed more favorable growth patterns and health indices than C. gariepinus. These findings suggest that environmental and biological factors such as food availability, reproductive status, and species-specific traits influence growth and condition. The study highlights the need for continuous monitoring and species-specific management strategies to enhance fishery productivity and sustainability in inland water bodies like Sabke Reservoir.
Keywords: Clarias gariepinus; Condition factor; Growth pattern; Length-weight; Oreochromis niloticus; Reservoir